Konsep Keadilan Peradilan Rasulullah Dan Relevansinya Dengan Peradilan Restoratif Di Indonesia - Irawan, Bambang; Amar, Zafran Arifah; Fadilah, Muhammad Rizky; Mawardi, Mawardi (Jurnal El-Thawalib, 2025)
Justice is the main goal in the justice system, both in the context of Islamic law and the national legal system. In Islamic history, the Prophet Muhammad SAW is known as a leader who not only conveyed revelations but also as a judge who upheld justice with wise, humanistic, and solution-oriented principles. This study focuses on the concept of justice in the trial of the Prophet Muhammad SAW, which prioritizes humanistic, rehabilitative, and non-discriminatory principles. This study is qualitative with a normative legal and comparative historical approach. Primary data sources from the Qur'an, Hadith, Islamic jurisprudence books, and sirah nabawiyah, which contain the practice of the Prophet's trial and regulations in Indonesia relating to restorative justice, and secondary sources come from scientific books, journals, and articles that discuss Islamic justice, the history of the Prophet's trial. The technique of collecting library data and analyzing it using qualitative descriptive techniques. The results of this study indicate that the concept of justice in the trial of the Prophet Muhammad SAW is very relevant to the principles of restorative justice in Indonesia because both emphasize dispute resolution through deliberation, restoration of social relations, and protection of the rights of victims and perpetrators in a balanced manner. The Prophet prioritized humanistic and solution-oriented justice, not merely punishment, as the approach now applied in the Indonesian legal system through various restorative justice policies.